Indian contract & specific relief acts - Pollock, Frederick, 1845-1937. (New Delhi : LexisNexis Butterworths, 1972)
Commentaries on Indian Contract Act, 1872 and Specific Relief Act, 1963
Keywords: India; India; Contracts -- India; Equitable remedies -- India